Research and Development: Designing BIPA Learning Materials of Riau Island Context for Foreign Students - Marsevani, Maya; Febria, Desty (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Indonesian 'Bahasa' is gaining popularity both within and outside of the country, being able to speak `Bahasa' is now highly advantageous. It is proved that an increasing number of foreign speakers are participating in the 'Program Bahasa Indonesia untuk Penutur Asing' (BIPA) or 'Bahasa' learning program. However, the current BIPA teaching materials contain several flaws and are therefore ineffective in aiding language acquisition. The aims of this study were to improve the efficiency of teaching Indonesian 'Bahasa' learning method at a university in Banal by using audio-visual aids, specifically for foreign students. The study discovered that it is essential to include interactive and culturally relevant resources in BIPA training, using research and development (RnD) methodologies using validity grid and interviews as the instrument. The validity score analyze based on the mean of each statement. After that, the interview was transcribed by researchers. The results of the study shed new light on the process used to create the University of Batam BIPA teaching materials book. An audio-visual Bahasa Indonesia textbook for BIPA was created with the intention of addressing unsolved difficulties by matching the content to the interests and requirements of the students. The outcomes also shown how creating an interactive BIPA textbook with audiovisual components and adding interactive sections may raise student interest and participation. BIPA learning may be brought closer to the objectives and skill levels of the learners by putting into practice efficient strategies to solve shortcomings that have been found and redesigning the instructional materials to increase interaction, diversity, and cultural relevance.